Effect of aluminum powder and NaOH on the physical and mechanical properties of aerated block with desulfurized gypsum. (11th June 2018) - Yong-qiang, Li; Hai-yan, Yu; Lie, Qu; Lei, Wang
ABSTRACT: In China, the desulfurization problem of power plants has been paid much attention by the government and the public. From 2014 to present, the nearly one hundred million tons of desulfurized gypsum has been discharged. The utilization rate of desulfurized gypsum in power plants has also become the focus of current research. The purpose of this study is to study the influence of aluminum powder and NaOH on the physical and mechanical properties of desulfurized gypsum aerated block(DGAB). The testing results show that when the optimized formula is 5% high-alumina cement, 0.7% aluminum powder, 0.5% NaOH, 0.6 water-cement ratio and the producing gas temperature is 40°C, the physical and mechanical properties of DGAB can reach the bulk density of 309.3 kg/m 3, the strength of 0.24 MPa, and the thermal conductivity of 0.073 W/(m·K). The microscopic analysis showed that when the amount of aluminum powder was 0.7%, the porosity of DGAB was minimum, its pore size was uniform and smaller than 1 mm, and the insulation effect was better. At this time, the strength of DGAB can reach the highest value and the thermal conductivity of DGAB is lower.